Analisis Bibliometrik Implementasi Kecerdasan Buatan dalam Ketenagakerjaan di Institusi Pendidikan - Dicka Widya Purnama; Candra Bagus Ainur Rochman; Rafli Darmawan; Putri Amaliyah; Achmad Dzikrul Baqi; Archam Zahidin; Renny Sari Dewi (J-INTECH ( Journal of Information and Technology), 2023)
Artificial Intelligence (AI) poses a challenge to the role of educators in the field of education, with the potential of being replaced by AI, which may reduce the relevance and sustainability of educators' roles. This research focuses on innovative solutions by implementing the Role Play Model and Project-Based Learning. The methodology employs systematic literature review with the assistance of biblioshiny. The results indicate that the implementation of the Role Play Model and Project-Based Learning by educators can mitigate the risk of replacement by AI. The active interaction and guidance provided by educators significantly contribute to students' understanding and skills, aspects that cannot be fully replaced by artificial intelligence. This study offers valuable insights to ensure the sustainability of educators' roles in the era of AI and digital transformation.